Electropolymerization on wireless electrodes towards conducting polymer microfibre networks - Yuki Koizumi (Nature Portfolio, 2016)
Electropolymerization of aromatic monomers on bipolar electrodes is emerging as promising route to the surface modification of conductive objects. Here, the authors discover that some conducting polymers propagate as fibres, opening up the possibility of growing conductive polymer networks via a wireless process.